Pathological and molecular investigation of porcine sapelovirus infection in naturally affected Indian pigs. (February 2019) - Kumari, Swati; Ray, P.K.; Singh, Rahul; Desingu, P.A.; Varshney, Rajat; Saikumar, G.
Abstract: The aim of the present study was to pathological and molecular investigation of porcine sapelovirus (PSV) in naturally infected Indian pigs of various age groups. Eight samples (16%) out of 49 necropsied animals were positive for PSV on the basis of pathological and molecular investigation. Major lesions of PSV positive cases were thickening and clouding of meninges, congestion in brain, severe to moderate congestion in lungs along with froathy exudates in trachea, thickening of intestinal mucosa, especially mucosal folds of ileum. Microscopic lesions of PSV positive cases in CNS were perivascular cuffing, neuronophagia and focal gliosis. In lungs, interstitial pneumonia was noticed in all cases, and intestinal lesions comprised of sloughing of villi epithelium, moderate to severe congestion of blood vessels and infiltration of mononuclear cells mainly plasma cells in both large and small intestine. RT-PCR results of total cases examined for PSV were targeted for PSV 3D Polymerase, 5′UTR region and VP1 gene respectively. Genetic characterization was done on the basis of viral capsid protein 1 (VP1) gene of PSV. The sequencing and phylogenetic analysis of amplified VP1 gene product showed maximum identity 85–90% with South Korean, KJ821021.1 and Indian, KY053835.1 strain of PSV. Further explorative surveillance and epidemiological studies are suggested to find out the real impact of this economically important disease affecting pigs population of India. Highlights: The present study was to pathological and molecular investigation of porcine sapelovirus (PSV) in Indian pigs of various age groups. Eight samples (16%) out of 49 necropsied animals were positive for PSV. The sequencing and phylogenetic analysis of amplified VP1 gene product showed maximum identity 85-90% with South Korean and Indian strain of PSV.